Conservation ecology of Irrawaddy dolphins in estuarine waters of Kuching - Andrew Alek, Tuen; Gianna, Minton; Cindy, Peter (UNIMAS Publisher, Universiti Malaysia Sarawak, 2020)
Cetaceans in the nearshore waters of Sarawak have ecological functions and economic importance to the state. Being the keystone species of the ocean, they are valuable as indicators of the health of the environment as they sit on top of the ocean’s food chain. The presence of marine mammals in an area indicate that the fishing stock of the particular area is still present. In addition to that, the Irrawaddy dolphins also serve as important attraction for the eco-tourism industry within Kuching Bay. However, populations of the Irrawaddy dolphins throughout South East Asia are facing risk of local extinction due to anthropogenic factors such as bycatch in fisheries, habitat loss and degradations, decreased fitness from pollutions or contaminants.